Teknologi Tepat Guna UMKM Kotim Kelompok Tani Kecamatan Mentaya Hilir Selatan - Rudy Setiawan; Mustaqiem Mustaqiem (Journal of Computer System and Informatics (JoSYC), 2020)
Information technology (IT) is a part of science, and technology in general is all technology related to information retrieval, collection, processing, storage and dissemination. In this case, the use of Information Technology (IT) has been widely used and utilized by the public, one of which is business actors or MSMEs. Appropriate Technology is technology that is in accordance with the conditions in which the technology is used or applied from social, economic, and cultural aspects. So that it can make business actors, in this case MSMEs, be more developed and forge themselves better in terms of capacity and business strategy so that they can certainly achieve success more easily. have excellent products. As for some of the products from MSMEs in the Mentaya Hilir Selatan District, including Samuda Village, Virgin Coconut Oil, Cooking Oil from Coconut, Kelulut Honey, and others. In running its business, the Mentaya Hilir Selatan District MSMEs that work with local farmers have several obstacles including the slow marketing of UMKM products due to a lack of promotional media and limited marketing areas and also MSME products in the Mentaya Hilir Selatan District itself are not well known by the community, causing slow products. sold. Therefore, to overcome this problem, a new computer-based system (programmed) was designed which functioned as a data processing medium, both employee data and transaction data